Consistent conjectures are optimal Cournot-Nash strategies in the meta-game. (2nd December 2017) - Kalashnikov, V. V.; Bulavsky, V. A.; Kalashnykova, N. I.; López-Ramos, F.
Abstract : In this paper, we investigate the properties of consistent conjectural variations equilibrium developed for a single-commodity oligopoly. Although, in general, the consistent conjectures are distinct from those of Cournot-Nash, we establish the following remarkable fact. Define a meta-game as such where the players are the same agents as in the original oligopoly but now using the conjectures as their strategies. Then the consistent conjectures of the original oligopoly game provide for the Cournot-Nash optimal strategies in the meta-game.